Effect of monochromatic light on self-renewal and differentiation of intestinal stem cells in broilers - Xinlei Tao; Ge Hu; Zixu Wang; Yaoxing Chen; Jing Cao (Poultry Science)
The maintenance of intestinal homeostasis relies on the continuous self-renewal and differentiation of intestinal stem cells (ISC). This study examines the effects of monochromatic light on the self-renewal and differentiation of ISC, thereby elucidating the mechanisms by which monochromatic light influences the growth and development of broilers. The post-hatching day 0 (P0) Cobb 500 broilers were randomly assigned to white light (WL), red light (RL), green light (GL) and blue light (BL) until P35. The findings indicated that the body weight of broilers in the BL group was significantly higher than that observed in the WL groups, and the BL group exhibited an increase in jejunal villus length, a decrease in crypt depth, and a reduction in the villus to crypt (V/C) ratio. The mRNA levels of Sglt1, Glut1, Slc7a5, Fabp2, sIgA, and Tff3 in the jejunum of the BL group were significantly increased relative to those in the other light groups. Furthermore, there was a notable increase in the number of enterocytes, goblet cells, Paneth cells, and enteroendocrine cells. The mRNA levels of Muc2, Lyz, Alpi and Chga as well as the protein levels of SI, Lyz and Chga were also significantly raised. Additionally, the BL group promoted the expression of PCNA and Lgr5, increased the mRNA levels of Olfm4 and Ccnd1, and elevated the protein levels of Lrp6 and β-catenin, while decreasing the protein level of APC. Meanwhile, BL group resulted in increased mRNA levels of Notch1, Notch2 and Dll4, along with an increase in the protein level of Notch1. Relative to the WL group, the BL group also enhanced the depth of cecal crypt and the number of PCNA immunoreactive cells, as well as increased the mRNA levels of Muc2, Chga, Lgr5, sIgA and Tff3. These results suggest that BL may facilitate the self-renewal and differentiation of ISC and enhance the morphology and function of the intestinal epithelium by activating the Wnt/β-catenin and Notch signaling pathways.